CHANGES IN PHYSICAL ACTIVITY ASSOCIATED WITH A NOVEL HEALTH AND WELLNESS PROGRAM FOR AT-RISK OLDER INDIVIDUALS. (11th November 2018) - Towne, S; Li, Y; Lee, S; Smith, M; Han, G; Du, Y; Benden, M; Ory, M
Abstract: Declines in moderate-to-vigorous physical activity (MVPA) is associated with increasing age, even though older adults have similar recommendations as those aged 18–64. Adults should engage in at least 150 minutes of moderate or 75 minutes of vigorous (or a combination MVPA) physical activity every week to have health-related benefits and help avoid costly preventable medical care. We examined the associated pre/post changes in MVPA (objective accelerometer-based measurement n=38) among adults engaging in a novel evidence-based program targeting community-dwelling middle-aged and older adults. The intervention was a 20-session (approximately 2 sessions/week) group-based class with in-class exercise and education included. Two timepoints were examined: baseline and immediate post intervention (the week following the last session of the intervention). Mean age of the accelerometer subgroup was 72 (range: 60–88) with 65% having two-or-more chronic conditions (comorbidities) with mean baseline minutes of MVPA at 140 minutes and immediate post minutes of MVPA at 165. When restricting the sample to those not meeting the recommended dose at baseline (<150 minutes of weekly MVPA), there was a mean of 51 minutes at baseline and 90 minutes at immediate post (chisq test: moderate effect size 0.4727, p=0.0210) indicating higher MVPA was found for intervention participants with <150 weekly MVPA at baseline. Novel interventions are needed to combat physical activity declines in older age, especially among those at-risk individuals failing to meet the recommended weekly minutes of MVPA. Interventions such as community-based health/wellness programs are one of many critical aides in this effort.